Penerjemahan Kata Sapaan Pada Novel Terjemahan Niji No Shounen Tachi (Terjemahan Dari Novel Laskar Pelangi) - Elmida Enggrayani; Hana Nimashita; Arza Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack : This study discusses about the translation of greeting word in the novel “Niji No Shounen Tachi” which is translated from the novel of Laskar pelangi. The Purpose of this study is to determine the method of translation and the procedures in translating the greeting words on the novel. The data is the entire word greeting contained in novel translation, and the greeting words between speaker and listener. This research is qualitative descriptive word translation which interpret greeting studied based on the theory of Peter Newmark (1988). The method is not only noted the use of verbal language but also the use of language of writing. After reading the greeting words contained in the novel of Laskar Pelangi, then the researcher look for the same data on novel translation in Niji No Shounen Tachi. After getting the data, the researchers analyze it by using the thoery of translation by Peter Newmark (1988). The result of this research gains from semantic translation method, communicative translation method, literal translation and adaptation. While the procedure of the translation use free modulation, analysis componen, shift, functional equivalent, cultural equivalent, reduction and expansion, and transference.Key Word : Translation, Greeting Word.